Defect Size Dependent Reconstruction Strategy of the Nasal Tip Cutaneous Wounds: A Retrospective Study - Wu M; Zhang X; Li A; Xu J; Dai H; Zhu J; Dong J; Chen K; Xiao Y; Wang Y; Xue C (Clinical, Cosmetic and Investigational Dermatology, 2025)
Minliang Wu,* Xinyi Zhang,* Ang Li,* Jianguo Xu, Haiying Dai, Ji Zhu, Jie Dong, Kexin Chen, Yuai Xiao, Yuchong Wang, Chunyu Xue Department of Plastic Surgery, Changhai Hospital, Naval Medical University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chunyu Xue, Department of Plastic Surgery, Changhai Hospital, Naval Medical University, 168 Changhai Road, Shanghai, 200433, People’s Republic of China, Email xcyfun@sina.com Yuchong Wang, Department of Plastic Surgery, Changhai Hospital, Naval Medical University, 168 Changhai Road, Shanghai, 200433, People’s Republic of China, Email drwangyc@163.comObjective: To achieve satisfying function and appearance of nasal tip after tumor resection.Methods: This retrospective study included patients with nasal tip tumors admitted between January 2010 and January 2024. A standardized data collection template was used to collect related variables. Tumors were all resected according to the guidelines, and the defects were repaired with different flaps. For nasal tip soft tissue defects smaller than 1 cm, a horn-shaped flap was used; for defects with a diameter of 1– 2 cm, the bilobed flap was applied; for defects larger than 2 cm, frontonasal flap was designed.Results: Twenty-eight patients were included in this study. All the skin defects were repaired according to the one-stage reconstruction strategy. All patients achieved primary healing without severe complications. Slight edema occurred in 5 patients, and slight infection occurred in 2 patients, all healed with dressing change in several days. Ideal aesthetic results achieved without distortion of the nasal tip or alar rim. During the follow-up period of 3– 11 months, no tumor occurrence was observed.Conclusion: The reconstruction strategy reported in this study is a promising way in the repair of nasal tip soft tissue defect with little complication and satisfying outcomes.Keywords: nasal tip defect, horn-shaped flap, bilobed flap, frontonasal flap, nasal reconstruction